2010
DOI: 10.1902/jop.2010.100321
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Chronic Periodontal Disease and Obesity: A Systematic Review and Meta‐Analysis

Abstract: Background Obesity is increasing in prevalence and is a major contributor to worldwide morbidity. One consequence of obesity might be an increased risk for periodontal disease, although periodontal inflammation might, in turn, exacerbate the metabolic syndrome, of which obesity is one component. This review aims to systematically compile the evidence of an obesity–periodontal disease relationship from epidemiologic studies and to derive a quantitative summary of the association between these disease states. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
358
7
31

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(446 citation statements)
references
References 124 publications
(323 reference statements)
26
358
7
31
Order By: Relevance
“…Obesity plays a role in modulating the initiation and progression of periodontal disease. Recent meta-analyses have validated a positive association between being overweight or obese and periodontitis 6,14,27) .…”
Section: Introductionmentioning
confidence: 99%
“…Obesity plays a role in modulating the initiation and progression of periodontal disease. Recent meta-analyses have validated a positive association between being overweight or obese and periodontitis 6,14,27) .…”
Section: Introductionmentioning
confidence: 99%
“…For this reason dentists need to be aware of implications of managing such patients. Previous studies have attempted to determine the dental need of overweight and obese adults 6,7,8 . Other authors have identified the challenges faced by clinicians when trying to provide safe dental care to this patient group 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, one study concluded that PD and abdominal obesity measured by WHR would not be associated 9 . It would be possible to explain this due to ethnic and anthropometric differences in the populations studied.…”
Section: Resultsmentioning
confidence: 99%
“…During the past few years, it has been described that the nutritional status has a negative effect on periodontal disease (PD) 8,9 , specifying that abdominal obesity would act as a risk factor (10). Due to the impact it generates on the metabolic and immune parameters, susceptibility of the host increases 11,12 favoring progression and severity of the disease.…”
Section: Introductionmentioning
confidence: 99%